The Relationship Between Gadget Usage and Adolescent Sleep Quality - Ivana, Indi; Murniati, Murniati; Ayu Trisno Putri, Noor Rochmah Ida (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction: Adolescent are very interested in gadgets that make it easier for them to carry out various social activities. One of the problems that can arise from gadget overuse is decreased quality of sleep. The purpose of this study was to determine the relationship between gadget usage behavior and adolescent sleep quality. Methods: Cross-sectional design was used in this study. Ninety-nine respondents had chosen with a proportionate stratified random sampling. Analysis was done by Chi square test. Results: Data analysis showed that 84.8% of the respondents were categorized as gadget addiction and 80.8% of the respondents experienced poor sleep quality. The relationship between gadget usage and sleep quality was significant with a p-value of 0.0001. Conclusion: There was a relationship between gadget usage and sleep quality in adolescents, in which gadget dependency had poorer quality of sleep.